A GIS TOOLKIT FOR AUTOMATING DESCRIPTIVE STATISTIC COMPUTATIONS FOR AIR QUALITY MODELING - Andreas Marios Georgiou; Themis Kontos (Geoplanning: Journal of Geomatics and Planning, 2018)
A GIS toolset was developed to support spatial analysis functions, visualization and extraction of a variety of input variables for air quality assessment. The developed toolset allows the automated processing of large amounts of ASCII data converting to points and raster data and the examination of the correlation among them. A case study was performed in Athens basin in Greece. Using the developed GIS toolset, topographic, climatic characteristics and air pollution conditions as well correlations were derived by processing the input data. In addition, thematic maps illustrating the spatial distribution of each parameter were extracted.  The developed GIS toolset greatly reduced the time and effort needed to process the GIS data, and provided a useful tool for a wide variety of environmental applications. The tool uses ArcObjects as the programming language to incorporate equations for statistical analysis in a monthly and a yearly time step. This versatile programming language allows advanced users to incorporate more complex formulations for more accurate results as detailed data is acquired to develop routines for calibration when reference data exist. Results verified the usefulness and feasibility of the developed platform.